Titania nanoparticles stabilized HPA in SBA-15 for the intermolecular hydroamination of activated olefins - Sawant-Dhuri, Dhanashri; Balasubramanian, Veerappan V.; Ariga, Katsuhiko; Park, Dae-Hwan; Choy, Jin-Ho; Cha, Wang Soo; Al-deyab, Salem S.; Halligudi, Shivappa B.; Vinu, Ajayan (ChemCatChem, 2014)
A liquid phase hydroamination (HA) of alpha,beta-ethylenic compounds with amines was investigated with TiO2 nanoparticles stabilized 12-tungstophosphoric acid (TPA) in SBA-15. The catalysts were prepared by wet impregnation of TPA/TiO2 nanoparticles into the SBA-15 and calcined at different temperatures. The characterization results reveal that the textural properties and the acidity of the prepared catalysts can be finely controlled with the simple adjustment of the calcination temperature and the structure of the support, decorated with the TiO2 and TPA nanoparticles, was intact even after the modification. The prepared catalysts were investigated for HA of ethyl acrylate with different aromatic and aliphatic amines over a wide range of reaction conditions to optimize the yield and the selectivity of product. It was found that this process is 100% atom efficient and the catalytic performance depended significantly on the loading of TPA over the catalyst and the calcination temperature. Under optimized reaction conditions, the best catalyst, 15 wt% TPA/22.4 wt% TiO2/SBA-15 calcined at 1123 K, offered the highest conversion of p-ethylaniline (70%) with 100% chemo-selectivity to the anti-Markovnikov product, i.e., the mono-addition product. The reaction was heterogeneously catalyzed and no contribution from leached TPA into the reaction was observed.
Keywords: heteropoly acids; hydroamination; mesoporous materials; nanocatalysts